ANALYSIS OF ECONOMIC GROWTH ON JAVA ISLAND - Maimunah, Maimunah; Rahmayanti, Dini; Kurniawan, Heri (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2024)
This research aims to determine the influence of Zakat, Inflation, Government Expenditures, and Exports on Economic Growth in Java Island. This research uses quantitative methods and the Eviews 10 tool, as well as data obtained from the Central Statistics Agency (BPS) and BAZNAS. The results show that Zakat has a significant positive effect on economic growth because Zakat helps many MSMEs obtain capital to run their businesses. Government spending has a significant positive effect on economic growth because government spending is used to support education and infrastructure on the island of Java, especially in large cities and regions that need education funds. Exports have a significant positive effect on economic growth because expanding exports can increase the country's foreign exchange and can add new jobs, while Inflation has no effect on economic growth on the island of Java because Inflation cannot be read and is too high can damage the economy in various circles.